Strategy To Improve Early Childhood Independence Through Story Method At KB Dewi Sartika Probolinggo - Urniwana, Siti; Khadavi, M Jadid; Agustiarini Eka Dheasari (Pijar Pelita: Journal of Early Childhood Education and Early Childhood Islamic Education, 2025)
ABSTRACT: Early childhood independence is an important aspect in child development that must be formed early on so that children are able to develop their ability to think, act, and make decisions independently. This study aims to determine the strategy for increasing early childhood independence through the story method at KB Dewi Sartika Probolinggo. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The informants in this study were the Head of the Foundation, Principal, teachers, students, and guardians. The results of the study showed that the story method has proven effective as a learning strategy to foster values ​​of independence in early childhood, such as the habit of tidying up their own toys, wearing clothes without help, and making decisions in daily activities. Teachers at KB Dewi Sartika Probolinggo utilize stories with characters that reflect an independent attitude as a means of conveying moral messages that are easy for children to understand. In addition, the involvement of teachers in discussions after telling stories helps children internalize the values ​​conveyed. So that the story method becomes an interesting and educational strategy in increasing the independence of early childhood at KB Dewi Sartika Probolinggo.